Trunk Muscle Coordination During Upward and Downward Reaching in Stroke Survivors - Gera, Geetanjali; McGlade, Kelsey E; Reisman, Darcy S; Scholz, John Peter (Motor control, 2016)
In this study, we investigated deficits in coordination of trunk muscle modes involved in the stabilization of the trunk's trajectory for reaching upward and downward beyond functional arm length. Trunk muscle activity from 10 stroke survivors (8 men, 2 women; 64.1 ± 10.5 years old) and 9 healthy control subjects (7 men, 2 women; 59.3 ± 9.3 years old) was analyzed. Coordination of trunk muscle modes to stabilize the trunk trajectory was investigated using the uncontrolled manifold (UCM) analysis. The UCM analysis decomposes the variability of muscle modes into good and bad variability. The good variability does not affect the control of trunk motion, whereas the bad variability does. In stroke survivors, deficits in the ability to flexibly combine trunk muscle modes was associated with reduced ability to minimize those combinations of trunk muscle modes that led to an error in trunk trajectory (bad variability), and this had a greater effect on reaching upward. This reduced coordination of trunk muscle modes during reaching was correlated with a clinical measure of trunk impairment.